Self-Control as a Mediator between Caregiver Burden and Quality of Life in Cancer Patient Primary Caregivers - Wanda Kiyah George Albert; Adi Fahrudin; Steward Lindong; Husmiati Yusuf (Islamic Guidance and Counseling Journal, 2023)
This study was conducted to identify the influence of the burden of care on the quality-of-life dimensions and examine the role of self-control as a mediator on the burden of care and the quality-of-life dimensions among primary caregivers of cancer patients who are in the terminal phase. This cross-sectional study involves 97 primary caregivers of terminal-phase cancer patients who were selected using purposeful sampling. The Adult Carer Quality of Life Questionnaire (AC-QoL), Zarit Burden Interview (J-ZBI-8), and Pearlin’s Sense of Mastery questionnaires were used in this study. Based on data analysis using Smart-PLS-Structural Equation Modeling (SEM) the direct analysis showed that subscale in care load, that is role strain had a significant negative influence on the quality of life in terms of support for caring, caring stress, personal growth, and the ability to care. Meanwhile, the subscale under the burden of care, that is personal strain, had a significant negative influence on the quality of life in terms of caring stress. Additionally, the analysis of indirect relationships revealed that self-control was found not to act as a mediator in the relationship between burden, caring stress and quality of life of the primary caregiver. This study has implications for the family of caregivers who experience the burden of care, especially in terms of role strain and personal strain, thus affecting several dimensions of their quality of life. Thus, in order to improve the quality of life among the primary caregivers of those cancer patients at the terminal stage, social workers in the helping profession field need to implement some appropriate approaches, methods, and techniques that will help to give sufficient mental, emotional, social and family support among the caregivers.